2009
DOI: 10.1590/s0034-89102009000800003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da estrutura dos centros de atenção psicossocial do município de São Paulo, SP

Abstract: OBJECTIVE:To describe infrastructure, human resources, and care approaches in psychosocial healthcare services. METHODS:Descriptive study including 21 psychossocial healthcare services for adults affi liated to the local health department in the city of São Paulo, Southeastern Brazil, conducted between 2007 and 2008. Information about infrastructure of facilities, human resources available and patient care was collected using a standardized instrument. There were performed descriptive data analysis and chi-squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
22

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 5 publications
0
10
0
22
Order By: Relevance
“…Surgem como uma possibilidade de assistência em uma proposta mais ampla de uma rede de cuidados em saúde mental, ou seja, a proposta de criação de um sistema de saúde que contemple a abordagem integral dos indivíduos e de suas famílias 3 . Diante da reorganização e ampliação dos serviços públicos em saúde mental com base nessa nova proposta de atenção ao portador de transtorno mental, se faz mister avaliar esses espaços tanto no tocante às ações desenvolvidas quanto à estrutura física, recursos humanos, condições de trabalho, dentre outras a fim de verificar a efetivação da função de reabilitação psicossocial designada aos CAPS 3,4 . A partir desse olhar crítico aos CAPS, com base na relação entre avaliação e gestão em saúde, reforça-se o papel da avaliação no processo de gestão, o qual fornece elementos de conhecimento que subsidiam a tomada de decisão, propiciando o aumento da eficiência, eficácia e efetividades das atividades desenvolvidas pelo serviço ou pela gestão 5 .…”
Section: R Bras CI Saúde 20(4):261-268 2016unclassified
“…Surgem como uma possibilidade de assistência em uma proposta mais ampla de uma rede de cuidados em saúde mental, ou seja, a proposta de criação de um sistema de saúde que contemple a abordagem integral dos indivíduos e de suas famílias 3 . Diante da reorganização e ampliação dos serviços públicos em saúde mental com base nessa nova proposta de atenção ao portador de transtorno mental, se faz mister avaliar esses espaços tanto no tocante às ações desenvolvidas quanto à estrutura física, recursos humanos, condições de trabalho, dentre outras a fim de verificar a efetivação da função de reabilitação psicossocial designada aos CAPS 3,4 . A partir desse olhar crítico aos CAPS, com base na relação entre avaliação e gestão em saúde, reforça-se o papel da avaliação no processo de gestão, o qual fornece elementos de conhecimento que subsidiam a tomada de decisão, propiciando o aumento da eficiência, eficácia e efetividades das atividades desenvolvidas pelo serviço ou pela gestão 5 .…”
Section: R Bras CI Saúde 20(4):261-268 2016unclassified
“…In a study carried out in the city of Sao Paulo, 9 SP, it was found that CAPS dealing with adults had great heterogeneity of organization and function between the different types of care. This diversity was attributed to the history of how mental health services in the city were established, to regional differences and to socioeconomic differences relating to health, cultural, sport and leisure resources in the area of each CAPS, to the varied composition of the teams and to the understanding of the activities according to the abilities of the individual professional.…”
mentioning
confidence: 99%
“…8 In view of these issues and also in view of the process of reorganization of the UHS and the mental health care network, several authors have already appraised the PSCC evaluation process with the purpose of evaluating the functioning of these services taking into consideration its physical structure, human resources, working conditions, satisfaction and overload of the health professional, among others. 9 From this perspective, satisfaction studies can contribute to the institutionalization of evaluation and reorganization of services, besides being a tool for the participation of health professionals. 10 Understanding the influence of the work organization on the quality of life, mental health, physical weariness and illnesses of workers becomes essential for understanding and intervening in work situations that can lead to various forms of suffering, illnesses and exclusion.…”
Section: Ntroductionmentioning
confidence: 99%